Pengaruh Discharge Planning Berbasis Keluarga Terhadap Kualitas Hidup Pasien Stroke : Literatur Review - Eka Wati; Ainul Yaqin Salam; Grido Handoko Sriyono (Pusat riset dan Inovasi Nasional, 2023)
Implementing family-based discharge planning, which relies on the participation of family members, can help stroke victims feel better. The purpose of this study was to identify the effect of family-based discharge planning on the quality of life of stroke patients based on journal literature reviews. Methode uses systematic literature reviews of journals taken from research in 15 journals, which were discovered through screening results of a number of journals from Google Scholar, Cochrane, Science Direct, Pubmed, and Wile using the keywords